2016
DOI: 10.1016/j.visres.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Rejecting probability summation for radial frequency patterns, not so Quick!

Abstract: Radial frequency (RF) patterns are used to assess how the visual system processes shape. They are thought to be detected globally. This is supported by studies that have found summation for RF patterns to be greater than what is possible if the parts were being independently detected and performance only then improved with an increasing number of cycles by probability summation between them. However, the model of probability summation employed in these previous studies was based on High Threshold Theory (HTT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(67 citation statements)
references
References 59 publications
6
57
4
Order By: Relevance
“…Although there is variation in the data, our results are consistent with Baldwin et al (2016) and with other work from our lab, which suggests no change in psychometric slopes with an increase in the number of cycles of modulation.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although there is variation in the data, our results are consistent with Baldwin et al (2016) and with other work from our lab, which suggests no change in psychometric slopes with an increase in the number of cycles of modulation.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have used high threshold theory (HTT) to provide an estimate of probability summation; however, evidence from Baldwin et al (2016) has suggested this is an inappropriate method for RF patterns. We have included it here to provide a comparison with previous works.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…
There is an ongoing debate over whether there is convincing evidence in support of global contour integration in shape discrimination tasks, particularly when using radial frequency (RF) patterns as stimuli (Baldwin, Schmidtmann, Kingdom, & Hess, 2016). The objection lies in the previous use of high-threshold theory (HTT), rather than signal detection theory (SDT) to model the probability summation estimates of observer thresholds to determine whether integration of information is occurring around the contour.
…”
mentioning
confidence: 99%